THE IMPACT OF THE ABOLITION OF THE SLAVE TRADE ON OMAN IN THE LATE 19TH CENTURY (1856-1913) - Asst. Prof. Dr. Bushra Nasser Hashim As-Saadi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Oman has gained special importance in the Arabian Gulf region throughout its long history. This is attributed to its distinctive geographical location in the Arabian Gulf region and the Arabian Sea. Oman has served as the southern gateway to the Gulf and a crossroads for international trade and navigation. This advantage has granted it experience in sea riding and carrying out important business activities between East Africa and South-West Asia, including the slave trade. The slave trade has been an important source of Oman’s economy from slaves imported from East Africa. The period (1856-1913) is selected, during which Oman after the death of Saeed bin Sultan is divided into two separate authorities, the first in Oman, its capital Muscat, and the second in East Africa, its capital Zanzibar. European countries, notably Britain and France, have contributed to establishing this division, arguing that it serves the case of the abolition of the illegal trade (the slave trade) in Oman. This study concluded that Britain and France had ended their competition for Oman by agreeing to transfer this case to the International Court of Justice and then to apply its decisions. It also found that abolishing the slave trade in Oman had resulted in several consequences for Britain. They included the practice of piracy through its naval fleet, so that none of the Omani ships dared to sail for fear of being inspected by the British fleet. This facilitated the extension of British influence in the Sultanate and the confiscation of goods on the Omani ships under the pretext of being on ships engaged in the slave trade. This in turn led to the economic exhaustion of Omani merchants.